Turbulence influence on wind energy extraction for a medium size vertical axis wind turbine. Issue 11 (18th February 2016) - Möllerström, Erik; Ottermo, Fredric; Goude, Anders; Eriksson, Sandra; Hylander, Jonny; Bernhoff, Hans
Abstract: The relation between power performance and turbulence intensity for a VAWT H‐rotor is studied using logged data from a 14 month (discontinuous) period with the H‐rotor operating in wind speeds up to 9 m/s. The turbine, designed originally for a nominal power of 200 kW, operated during this period mostly in a restricted mode due to mechanical concerns, reaching power levels up to about 80 kW. Two different approaches are used for presenting results, one that can be compared to power curves consistent with the International Electrotechnical Commission (IEC) standard and one that allows isolating the effect of turbulence from the cubic variation of power with wind speed. Accounting for this effect, the turbine still shows slightly higher efficiency at higher turbulence, proposing that the H‐rotor is well suited for wind sites with turbulent winds. The operational data are also used to create a Cp ( λ) curve, showing slightly lower Cp compared with a curve simulated by a double multiple streamtube model. Copyright © 2016 John Wiley & Sons, Ltd.